2011
DOI: 10.1007/s10681-011-0597-5
|View full text |Cite
|
Sign up to set email alerts
|

The plant size and the spine characteristics of the first generation progeny obtained through the cross-pollination of different genotypes of Cactaceae

Abstract: The main characteristics (plant diameter, number of spine/areoles and length of spines) of 16 cactus hybrids were analysed and the genetic variability and broad-sense heritability was studied. The descendants were obtained through a cyclic crosspollination pattern, with the parental forms chosen based on aesthetic considerations. Cross-pollination among Rebutia senilis 9 Aylostera muscula, Rebutia tarvitaensis 9 Aylostera muscula, Aylostera flavistyla 9 Rebutia senilis, Rebutia senilis 9 Aylostera flavistyla, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…On the other hand, S l and S a were the most variable spine traits. In another study, spine length was also found to be the most variable trait in 30 Aylostera and Rebutia ( Cactoideae ) hybrids ( Mihalte and Sestras 2012 ). It has already been found that spine variation occurs even within a single species, reflecting environmental conditions during cactus growth (e.g.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, S l and S a were the most variable spine traits. In another study, spine length was also found to be the most variable trait in 30 Aylostera and Rebutia ( Cactoideae ) hybrids ( Mihalte and Sestras 2012 ). It has already been found that spine variation occurs even within a single species, reflecting environmental conditions during cactus growth (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…Hunt et al 2006 , Mosco 2009 , Řepka and Gebauer 2012 ). Although, there is evidence that spine development is influenced by genetic ( Mihalte and Sestras 2012 ) and environmental conditions as water availability or solar radiation can modified spine growth (e.g. Peharec et al 2010 , Menezes et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…An implicit assumption that these traits are innate (or at least widely influenced by genetics) underlies their use in taxonomy. Although, there is some evidence that they are inheritable (Mihalte and Sestras, 2012), the factors involved with spine and rib morphogenesis are still poorly known (Mauseth, 2006). Furthermore, it is also known that spine and rib traits can be influenced by the environment, including growth conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%